2015
DOI: 10.1007/s00125-015-3783-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in the age-associated decline of pancreatic beta cell function in rat islets

Abstract: Aims/hypothesisAgeing can lead to reduced insulin sensitivity and loss of pancreatic beta cell function, predisposing individuals to the development of diabetes. The aim of this study was to assess the contribution of microRNAs (miRNAs) to age-associated beta cell dysfunction.MethodsThe global mRNA and miRNA profiles of 3- and 12-month-old rat islets were collected by microarray. The functional impact of age-associated differences in miRNA expression was investigated by mimicking the observed changes in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
2
40
1
Order By: Relevance
“…Moreover, an ageing-associated upregulation of miR-34a, miR-124a and miR-383, and downregulations of miR-130b and miR-181a were found in the pancreas of 12-month-old rats [43]. Importantly, besides the well-established age-induced modification of gut microbiota [44], clear evidences between the link of pancreas health and sensing of microbial antigens have been provided by several publications.…”
Section: Pancreatic Mirsmentioning
confidence: 94%
“…Moreover, an ageing-associated upregulation of miR-34a, miR-124a and miR-383, and downregulations of miR-130b and miR-181a were found in the pancreas of 12-month-old rats [43]. Importantly, besides the well-established age-induced modification of gut microbiota [44], clear evidences between the link of pancreas health and sensing of microbial antigens have been provided by several publications.…”
Section: Pancreatic Mirsmentioning
confidence: 94%
“…Glu, glucose; Pyr, pyruvate; Lac, lactate; Glut, glutamante; Orn, ornitine; PolII, RNA polymerase II; Mito, mitochondria. Data source: Pullen et al (2011), Klein et al (2013), Liang et al (2015), Martinez-Sanchez et al (2015), Tugay et al (2016). See the main text for further details.…”
Section: Mirnas and Disallowed Genesmentioning
confidence: 99%
“…Indeed, Pdgfra is an experimentally validated target for miR-34a in pulmonary artery smooth muscle and colon cancer cells and glioblastoma (Genovese et al, 2012; Li C. et al, 2015; Wang P. et al, 2016), miR-130a during mesodermal specification (Singh et al, 2015), miR-146b-5p in blood cells and hepatocellular carcinoma (Zhu et al, 2013; Zhai et al, 2014) and miR-140 during palatogenesis (Eberhart et al, 2008). Moreover, the Regazzi laboratory, in collaboration with ourselves, has very recently demonstrated that miR-34a targets Pdgfra in rat islet cells (Tugay et al, 2016). As discuss below, miR-34a expression increases with age in rat and human islets and might thus be involved in the age-related decline in β-cell proliferation through its target Pdgfra (Tugay et al, 2016).…”
Section: Mirnas and Disallowed Genesmentioning
confidence: 99%
“…MiR-30a has been associated with glucotoxicity-induced defects in insulin secretion17. A role for miR-34a has also been repeatedly reported in both type 1 and type 2 diabetes as well as in age-associated diabetes212223. The effects of miR-375 , miR-30a , and miR-34a have been examined in pancreatic islet cells under diabetic conditions, but their contributions to a specific pathway have never been reported.…”
mentioning
confidence: 99%